Estimating the Actual Evapotranspiration of Different Vegetation Types Based on Root Distribution Functions - Dong, Zhiqiang; Hu, Hongchang; Wei, Zhongwang; Liu, Yaping; Xu, Hanlin; Yan, Hong; Chen, Lajiao; Li, Haoqian; Khan, Mohd Yawar Ali (Frontiers in Earth Science, 2022)
Background and aims Evapotranspiration (ET) is an important part of the water cycle and energy cycle. However, even under the same climatic condition, there are spatial differences in actual evapotranspiration (ETa) due to different land use and land cover. To characterize the influence of different vegetation types on ETa in China, this study parameterized the vertical distribution of the root systems of different vegetation types. Methods A one-dimensional soil-plant-atmosphere continuum (SPAC) model was constructed, and these root distribution functions were used to improve the root water absorption modulus of the SPAC model. Based on the improved model, the actual evaporation (Ea), actual transpiration (Ta) and ETa under different vegetation types were calculated, and the reasons for different ETa of different vegetation types were analyzed. Results The results show that the root distribution of all vegetation types increase first and then decrease as the depth increases, and almost all the maximum values are in the range of 0-20 cm. The savanna has the shallowest root system, while the barren has the deepest root system. The average ETa calculated in China is about 342.2mm/y in 2015. The average ETa of the broadleaf evergreen forests is the largest, about 773 mm/y and the barren is the smallest, about 151 mm/y. The average annual precipitation is the most important factor affecting the ETa differences of different vegetation types. Conclusions The results provide solutions for estimating the ETa of different vegetation types and are significant to water resources management and soil and water conservation.